Optimization and Validation of Caffeine in Robusta Coffee (Coffea canephora), Black Tea (Camellia sinensis), and Cocoa (Theobroma cacao L.) Using RP-HPLC Liquid-liquid Extraction - Lindawati Setyaningrum; Aliyah Purwanti; Dina Trianggaluh Fauziah; Retno Eka Lestari; Dyah Purwaningtyas; Sindi Anggraiyani; Muhammad Yuwono (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2026)
Caffeine, an alkaloid compound naturally found in various consumer products, has become the focus of increasing research in the analysis of products such as black tea, cocoa, and coffee. The chemicals found in coffee, cocoa, and black tea have pharmacological actions including antiviral, antihypertensive, antidiabetic, antioxidant, and hepatoprotective effects against hepatitis B. The chemical components include caffeine, theobromine, theophylline, tannins, adenine, vitamins (including vitamin C), flavonoids, methylxanthine, naringenin, and polyphenols. The resultant viscous extract was mixed with 25 milliliters of chloroform and 1.5 grams of CaCO3 in a separatory funnel and stirred. Three times, chloroform solution was added. The HPLC analytical method requires a wavelength of 272 nm, a methanol: redistilled water (70:30) mobile phase, and a flow rate of 1.0 mL/min to be validated. Results show resolutions of 1.49 and 1.57 for selectivity values, linearity of r = 0.9994, LOD 8.511 ppm and LOQ 28.370 ppm, accuracy of 99–101% for average recovery value, and precision of %The RSD level is 0.0095%. The results of the caffeine content determination test showed that the ethanol extract of robusta coffee beans obtained from the caffeine content ± SD obtained was 9.682 ± 1.254, black tea 34.525 ± 0.064, and cacao 6.890 ± 0.488.